OCCURRENCE OF THUNDERSTORM AND RAINFALL OVER PUNJAB, PAKISTAN (1961-2010) - Sadiq, N. (The Nucleus, 2013)
Occurrence of Thunderstorms (TS) and Rainfalls (RF) are contemplated via monthly, station wise seasonal and overall seasonal percentage analyses for all over the Punjab. Fifty years (1961-2010) data of the mentioned parameters for thirteen meteorological stations, uniformly distributed over the province, were utilized in this study. Monthly study has revealed the highest activity of TS and RF in the two months of monsoon (July and August) while rainfall occurrence acquired second highest frequency in the end of winter (March). Overall seasonal analysis shows markedly high activity of TS and RF in premonsoon and monsoon season while in winter RF frequency is almost twofold than TF. Further, rainfall yield in post-monsoon and winter season is comparable but TS activity is highly variable. Station wise seasonal analysis of winter explore that all stations acquire much more RF accompanied with little TS activity. The situation is altogether different for premonsoon and monsoon, while for post-monsoon it is composite. The results of this paper will help to provide updated cogitative assistance not only to the people concerned with the science, art or business of cultivating the soil but also to the community concerned with weather, aviation and planning.